The effects of 10-week plyometric training program on athletic performance in youth female handball players - Gaamouri, Nawel; Hammami, Mehrez; Cherni, Yosser; Rosemann, Thomas; Knechtle, Beat; Chelly, Mohamed Souhaiel; van den Tillaar, Roland (Frontiers in Sports and Active Living, 2023)
The aim of the study was to investigate the effects of a 10-week plyometric training (PT) on changes of direction, jumping ability, repeated sprint ability, and both muscular strength and power in youth female handball players. Twenty-eight participants (age: 15.8±0.2 years) were randomly divided into a plyometric group (PG; n=14) or a control group (CG; n=14). Significant (group×time) interaction was noted for change of direction (COD) [(Modified agility T-test (T-half)], three jumping tests [(squat jump (SJ), countermovement jump (CMJ) and standing long jump (SLJ)], repeated sprint ability (RSA), muscular strength [1-RM bench press and 1-RM half squat] and muscular power [force-velocity test for both upper and lower limb]. With a group×time interaction, the PG enhanced the T-half performance [p<0.001, ∆=10.4, d=1.95 (large)] compared to the CG. The PG enhanced the jump performance over SJ [p=0.009, ∆=18.3, d=0.72 (medium)], CMJ [p =0.005, ∆=20.7, d=0.79 (medium)] and SLJ [p<0.001, ∆=24.5, d=2.25 (large)]. Three of four RSA scores increased significantly in the PG compared to the CG [p<0.001, ∆=2.76, d=1.11 (large); p<0.001, ∆=2.72, d=1.23 (large); and p<0.001, ∆=2.75, d=1.21 (large), in best time (RSA-BT), mean time (RSA-MT) and total time(RSA-TT), respectively]. In contrast, group×time interactions revealed no significant differences in both 1-RM bench press and 1-RM half squat performance between PG and CG.Regarding the force velocity performance, the PG enhanced 3 of 4 force velocity scores for the upper limb performance [p<0.001, d=1 (large); p<0.001, d=1.13 (large) and p=0.012, d=0.72 (medium) for the peak power in these two forms (W and W•kg-1), and maximal pedalling velocity, respectively], and 2 of 4 force velocity scores for the lower limb performance [p=0. 045, d=0.56 (medium); and p=0.021, d=0.65 (medium) for the peak power in these two forms (W and W•kg-1), respectively]. It was concluded that additional PT performed two times3 per week during 10 weeks enhances measures related to game performance, such as COD, jump ability, RSA, and power in youth female handball players.